2006
DOI: 10.1179/016164106x130461
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and risk of dementia in non-demented elderly subjects with and without mild cognitive impairment

Abstract: Current diagnostic criteria for MCI subtypes define heterogeneous populations, but atrial fibrillation can be useful in identifying people with increased risk of conversion to dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…The study demonstrated that the presence of AF was associated with cognitive and functional decline and increased the risk of dementia by 30% [6]. Forti et al reported that AF was not significantly associated with the occurrence of dementia in patients with normal cognitive functions at baseline [22].…”
Section: Atrial Fibrillation and Dementiamentioning
confidence: 96%
“…The study demonstrated that the presence of AF was associated with cognitive and functional decline and increased the risk of dementia by 30% [6]. Forti et al reported that AF was not significantly associated with the occurrence of dementia in patients with normal cognitive functions at baseline [22].…”
Section: Atrial Fibrillation and Dementiamentioning
confidence: 96%
“…[80] Atrial fibrillation also appears to involve a significant conversion to dementia in nondemented subjects whether or not cognitive impairment was present. [81,82] Many studies have shown that atrial fibrillation induces significant brain hypoperfusion [83] which can compromise the aging cerebrovasculature. Although the true mechanism that associates AF to cognitive impairment is unclear, a suspicion is that cerebral hypoperfusion may be triggered by the chronic arrhythmia that is present.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…More physical activity 82 , low Body Mass Index (BMI) 27 or atrial fibrillation 83 predicted conversion from any type MCI to all cause dementia in clinical studies. "Antidementia drugs" reduced the risk of conversion from any type MCI to all cause dementia in a clinical 84 , but not in a higher quality epidemiological study 25 .…”
Section: Other Significant Predictorsmentioning
confidence: 99%